2010
DOI: 10.1152/ajpgi.00055.2010
|View full text |Cite
|
Sign up to set email alerts
|

Gene ablation for PEPT1 in mice abolishes the effects of dipeptides on small intestinal fluid absorption, short-circuit current, and intracellular pH

Abstract: PEPT1 function in mouse intestine has not been assessed by means of electrophysiology and methods to assess its role in intracellular pH and fluid homeostasis. Therefore, the effects of the dipeptide glycilsarcosin (Gly-Sar) on jejunal fluid absorption and villous enterocyte intracellular pH (pH(i)) in vivo, as well as on enterocyte[(14)C]Gly-Sar uptake, short-circuit current (I(sc)) response, and enterocyte pH(i) in vitro were determined in wild-type and PEPT1-deficient mice and in mice lacking PEPT1. Immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 46 publications
(62 reference statements)
2
60
0
1
Order By: Relevance
“…However, the intestinal peptide uptake with subsequent intracellular hydrolysis has been demonstrated to be a driving force for water uptake (1). And the PEPT1-mediated di-and tripeptide absorption has been shown in this context to be accompanied by a substantial concomitant salt and fluid absorption (6). Evidence for this role was also demonstrated here based on increased water content on feces of Pept1 Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 61%
“…However, the intestinal peptide uptake with subsequent intracellular hydrolysis has been demonstrated to be a driving force for water uptake (1). And the PEPT1-mediated di-and tripeptide absorption has been shown in this context to be accompanied by a substantial concomitant salt and fluid absorption (6). Evidence for this role was also demonstrated here based on increased water content on feces of Pept1 Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 61%
“…NHE3 is essential for PEPT1 activity by exporting protons back to the lumen, leading to the recovery of pH in from the acid load. As reported previously, PEPT1-deficient mice have impaired intestinal fluid absorption that is mediated via NHE3 in concert with a chloride-bicarbonate exchange system (5). This impairment in water absorption could also contribute to the observed dietindiced obesity (DIO) resistance phenotype.…”
Section: Discussionmentioning
confidence: 74%
“…PEPT1 is mainly expressed in the small intestine with higher levels in the proximal parts than in distal regions. Studies employing Pept1 Ϫ/Ϫ mice have demonstrated a lack of intestinal transport of model dipeptides such as glycylsarcosine (5,15), but animals otherwise do not show any obvious phenotypic alterations (21,22). We here provide on the analysis of changes in the gastrointestinal tract and of other phenotypic measures in mice deficient of PEPT1 when the animals are fed a diet containing 48 energy% from fat (HFD) compared with a high-carbohydrate/low-fat diet (13 energy% fat).…”
mentioning
confidence: 99%
“…Thus, it is obvious that in situ intestinal perfusions, although mechanistically valid, do not necessarily reflect expected outcomes under physiological in vivo conditions in which luminal drug concentrations and gastrointestinal residence times are operative. Other mechanisms (e.g., passive permeability and paracellular permeability), as suggested by Chen et al (2010) using everted jejunal sacs, may play a bigger role in the in vivo absorption of GlySar than previously believed, especially in the absence of PEPT1. GlySar is sufficiently small (mol.…”
Section: In Vivo Oral Absorption and Disposition Of Glycylsarcosinementioning
confidence: 83%